Analisis Pendekatan Komunikatif Dalam Teks Bahasa Inggris - Nur Azmi Rohimajaya (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
The objective of the research is to obtain information about the implementation of communicative approach in English textbook. The research methodology in this research is content analysis and the main instruments are text analysis, observation, interview and documentation. Based on the result of the research, it is concluded that communicative approach has been implemented in the design and organization of English textbook. Communicative syllabus has been used as a guideline in creating the organization of the book and each unit. Language content and language style are appropriate with student’s need. The goal of classroom activities focuses on communicative competence. Topic has been selected carefully to ensure that they match the student’s need and interest. The methodology in teaching grammar inductively is also the implementation of communicative approach. The conclusion of this research can be said that English textbook uses communicative approach based on design and organization, language content, topic, skill, and methodology, whereas the suggestions of this research are English textbook should be appropriate with student’s need, give grammar rules clearly, have accessories package completely, topic should be variety and provide more activities or skills that appropriate with the demand of curriculum.